Morphological Differences between the First and Second Permanent Upper Molars - Genaro, Luis Eduardo; Ferreira, Gabriely; Conte, Marcelo Brito; Gonçalves, Marcela de Almeida; Capote, Ticiana Sidorenko Oliveira (Journal of Morphological Sciences, 2019)
The dental elements present similar and specific anatomical features, depending on the functions they have in the oral cavity. The permanent molars are the most complex structures, mainly the occlusal face, due to their function of food grinding. The aim of the present article is to present the upper first and second molars morphology, emphasizing the similarities and differences between them. Besides, the upper first and second molars of the collection of the Department of Morphology of Universidade Estadual de Paulista (UNESP), School of Dentistry, Araraquara, were evaluated regarding the presence of the oblique ridge, frequency and classification of the molar tubercle, and the crown morphology (upper second molars). In the 372 evaluated upper first molars, the molar tubercle was absent in most of the teeth. When present, the molar tubercle belonged to the mesiolingual cusp; 8.9% were classified as type I; 9.1% as type II; and 9.4% as type III. The oblique ridge was present in all upper first molars. The morphology of 401 upper second molars was also evaluated; 64.83% were tetracuspid; 35.16% tricuspid; and 17.02% presented compression morphology. In 100 tricuspid teeth, 50% presented oblique ridge, with it being prominent in 30%. No upper second molars presented molar tubercle. Although there are similarities between the upper first and second molars, we must always be aware of the features that differ between them, so their functionality can be restored.
Keywords: anatomy and anthropology; education in morphology; macroscopic human anatomy